A cross-sectional study on depression and its associated factors among rural elderly in Chengalpattu District, Tamil Nadu - Ramesh Anshul; Ashokkumar Vikram; Sankar Karthik; Deepak Avinash KR; Mani Ezhilvanan; Chinnaian Sivagurunathan (Asian Journal of Medical Sciences, 2025)
Background: People around the world are living longer in the modern medicine era, often accompanied by challenges such as loneliness, neglect, and abuse impacting mental health. Depression is a common mental health condition among the elderly, frequently under-recognized and undertreated. Aims and Objectives: This study aimed to estimate the prevalence of depression among rural elderly individuals in Chengalpattu district, Tamil Nadu, India, and identify the associated sociodemographic factors. Materials and Methods: This community-based cross-sectional study was conducted among 390 eligible individuals aged 60 years and above residing in rural field practice areas of a private medical college. A pre-tested, semi-structured interview schedule was used, including sociodemographic questions and the 30-item geriatric depression scale. Data were analyzed using Statistical Package for Social Sciences v21.0, employing descriptive statistics, Chi-square tests, and binary logistic regression. Results: The study revealed that 33.8% of participants had mild/moderate depression, and 10.8% had severe depression. Age group, marital status, working status, presence of chronic diseases, history of abuse/violence/neglect, and role as a decision-maker in the family were found to be significantly associated with depression. Logistic regression showed that currently, working elderly individuals had higher odds of depression. Elderly experiencing abuse/violence/neglect showed a trend toward higher odds of depression, and those whose decision-making role declined showed a trend toward lower odds of depression. Conclusion: This study highlights the substantial prevalence of depression among rural elderly individuals and identifies several associated sociodemographic factors. These findings emphasize the need for community-level screening programs, counseling services, and strengthened rural health systems with adequate resources and infrastructure to provide targeted interventions and social support for the elderly, promoting their overall well-being.